Swallow Motor Pattern Is Modulated by Fixed or Stochastic Alterations in Afferent Feedback - King, Suzanne N.; Shen, Tabitha Y.; Musselwhite, M. Nicholas; Huff, Alyssa; Reed, Mitchell D.; Poliacek, Ivan; Howland, Dena R.; Dixon, Warren; Morris, Kendall F.; Bolser, Donald C.; Iceman, Kimberly E.; Pitts, Teresa (Frontiers in Human Neuroscience, 2020)
Afferent feedback can appreciably alter the pharyngeal phase of swallow. In order to measure the stability of the swallow motor pattern during several types of alterations in afferent feedback, we assessed swallow during a conventional water challenge in four anesthetized cats, and compared that to swallows induced by fixed (20 Hz) and stochastic (1-20Hz) electrical stimulation applied to the superior laryngeal nerve. The swallow motor patterns were evaluated by electromyographic activity (EMG) of eight muscles, based on their functional significance: laryngeal elevators (mylohyoid, geniohyoid, and thyrohyoid); laryngeal adductor (thyroarytenoid); inferior pharyngeal constrictor (thyropharyngeus); upper esophageal sphincter (cricopharyngeus); and inspiratory activity (parasternal and costal diaphragm). Both the fixed and stochastic electrical stimulation paradigms increased activity of the laryngeal elevators, produced short-term facilitation evidenced by increasing swallow durations over the stimulus period, and conversely inhibited swallow-related diaphragm activity. Both the fixed and stochastic stimulus conditions also increased specific EMG amplitudes, which never occurred with the water challenges. Stochastic stimulation increased swallow excitability, as measured by an increase in the number of swallows produced. Consistent with our previous results, changes in the swallow motor pattern for pairs of muscles were only sometimes correlated with each other. We conclude that alterations in afferent feedback produced particular variations of the swallow motor pattern. We hypothesize that specific SLN feedback might modulate the swallow central pattern generator during aberrant feeding conditions (food/liquid entering the airway), which may protect the airway and serve as potentially important clinical diagnostic indicators.